1989
DOI: 10.1007/bf01002469
|View full text |Cite
|
Sign up to set email alerts
|

Lectin-binding pattern of neuroepithelial and respiratory epithelial cells in the mouse nasal cavity

Abstract: Sections from the nasal cavity of 12-day-old Swiss albino mice (NMRI strain) were subjected to lectin histochemistry. A panel of biotinylated lectins (Con A, WGA, s-WGA, PNA, SBA, DBA and UEA I) and a horseradish peroxidase-conjugated lectin (GSA II) showed marked differences in binding to the respiratory and the neuroepithelial cells. SBA (affinity for galactose and N-acetylgalactosamine), PNA (galactose) and WGA (sialic acids and N-acetylglucosamine) labelled the receptor neurons in the olfactory and vomeron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
33
2

Year Published

1991
1991
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(44 citation statements)
references
References 32 publications
9
33
2
Order By: Relevance
“…The present results on the free borders, dendrites and cell bodies of the receptor cells are contrary to the previous reports that a larger number of lectins bound to the free border, dendrites and cell bodies of the receptor cells in the vomeronasal organ than those in the olfactory epithelium in the rodents [20,25,27]. This finding suggests that the vomeronasal organ is less active in some physiological functions, including signal transduction, with which sugar residues are associated, than the olfactory epithelium in the common marmoset unlike the rodents.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…The present results on the free borders, dendrites and cell bodies of the receptor cells are contrary to the previous reports that a larger number of lectins bound to the free border, dendrites and cell bodies of the receptor cells in the vomeronasal organ than those in the olfactory epithelium in the rodents [20,25,27]. This finding suggests that the vomeronasal organ is less active in some physiological functions, including signal transduction, with which sugar residues are associated, than the olfactory epithelium in the common marmoset unlike the rodents.…”
Section: Discussioncontrasting
confidence: 99%
“…Odorant or pheromonal molecules are thought to bind to their receptor sites on the cilia or microvilli on the free border to induce olfactory or vomeronasal transduction, respectively [3,4,17]. Since previous studies reported that the olfactory receptor cells were stimulated by volatile chemicals and the vomeronasal receptor cells responded mainly to non-volatile odorant stimuli [16,34], the difference of the sugar residues expressed on the free border between the olfactory epithelium and vomeronasal organ may reflect the difference of the property of odor received by the olfactory epithelium and vomeronasal organ as described by Lundh et al [20].…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…In humans, the syndrome of post-viral olfactory dysfunction (PVOD), consisting of olfactory loss and/or histological alterations in the olfactory epithelium, has been described following infections with respiratory viruses [34][35][36]. With respect to sialic-acid receptor expression patterns on ORNs, it has been shown that mouse ORNs can be stained with a pattern of lectins which recognize galactose, N-acetylgalactosamine and sialic acids, although subtypes and expression on human ORNs have not been determined [37].…”
Section: Introductionmentioning
confidence: 99%